NBR1-p62-Nrf2 mediates the anti-pulmonary fibrosis effects of protodioscin - Qian Zeng; Bin-bin Wen; Xin Liu; Yong-yu Luo; Zhen-gang Hu; Lei Huang; Xiao-hua Zhang; Xiao-ting Huang; Ting-ting Zhou; Xiao-xue Sang; Yu-yang Luo; Da-yan Xiong; et al. (BMC, 2024)
Abstract Background Idiopathic pulmonary fibrosis is a persistent disease of the lung interstitium for which there is no efficacious pharmacological therapy. Protodioscin, a steroidal saponin, possesses diverse pharmacological properties; however, its function in pulmonary fibrosis is yet to be established. Hence, in this investigation, it was attempted to figure out the anti-pulmonary fibrosis influences of protodioscin and its pharmacological properties related to oxidative stress. Methods A mouse lung fibrosis model was generated using tracheal injections of bleomycin, followed by intraperitoneal injection of different concentrations of protodioscin, and the levels of oxidative stress and fibrosis were detected in the lungs. Multiple fibroblasts were treated with TGF-β to induce their transition to myofibroblasts. It was attempted to quantify myofibroblast markers' expression levels and reactive oxygen species levels as well as Nrf2 activation after co-incubation of TGF-β with fibroblasts and different concentrations of protodioscin. The influence of protodioscin on the expression and phosphorylation of p62, which is associated with Nrf2 activation, were detected, and p62 related genes were predicted by STRING database. The effects of Nrf2 inhibitor or silencing of the Nrf2, p62 and NBR1 genes, respectively, on the activation of Nrf2 by protodioscin were examined. The associations between p62, NBR1, and Keap1 in the activation of Nrf2 by protodioscin was demonstrated using a co-IP assay. Nrf2 inhibitor were used when protodioscin was treated in mice with pulmonary fibrosis and lung tissue fibrosis and oxidative stress levels were detected. Results In vivo, protodioscin decreased the levels of fibrosis markers and oxidative stress markers and activated Nrf2 in mice with pulmonary fibrosis, and these effects were inhibited by Nrf2 inhibitor. In vitro, protodioscin decreased the levels of myofibroblast markers and oxidative stress markers during myofibroblast transition and promoted Nrf2 downstream gene expression, with reversal of these effects after Nrf2, p62 and NBR1 genes were silenced or Nrf2 inhibitors were used, respectively. Protodioscin promoted the binding of NBR1 to p62 and Keap1, thereby reducing Keap1-Nrf2 binding. Conclusion The NBR1-p62-Nrf2 axis is targeted by protodioscin to reduce oxidative stress and inhibit pulmonary fibrosis. Graphical Abstract